2016
DOI: 10.1071/wr16056
|View full text |Cite
|
Sign up to set email alerts
|

Density and activity patterns of pumas in hunted and non-hunted areas in central Argentina

Abstract: Context Hunting has demographic effects on large and medium carnivores, causing population reductions and even extinctions worldwide. Yet, there is little information on carnivore demographic parameters and spatial and temporal land-use patterns in areas experiencing sport hunting, thus hindering effective conservation plans for such areas. Aims We estimated densities and determined activity patterns of pumas (Puma concolor) from camera-trapping surveys in a protected area and in a game reserve with sport hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…In addition to increasing understanding of the role of migration in predator-prey dynamics in this system, baseline data on densities of pumas are important for conservation and management. Pumas are heavily controlled outside protected areas in Patagonia because of their impact on livestock, and sport hunting occurs in some regions of Argentina [ 41 , 82 ]. For elusive species such as pumas, obtaining density estimates can be challenging, particularly in non-forested habitats that lack trails and roads to help guide animals between cameras.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to increasing understanding of the role of migration in predator-prey dynamics in this system, baseline data on densities of pumas are important for conservation and management. Pumas are heavily controlled outside protected areas in Patagonia because of their impact on livestock, and sport hunting occurs in some regions of Argentina [ 41 , 82 ]. For elusive species such as pumas, obtaining density estimates can be challenging, particularly in non-forested habitats that lack trails and roads to help guide animals between cameras.…”
Section: Discussionmentioning
confidence: 99%
“…For elusive species such as pumas, obtaining density estimates can be challenging, particularly in non-forested habitats that lack trails and roads to help guide animals between cameras. To date, only a few studies have used spatial mark-resight models to estimate densities for pumas (e.g., [ 32 , 41 , 83 ]. However, comparisons of approaches for estimating density in tropical and subtropical forests demonstrated that traditional non-spatial approaches likely over estimate densities and that a mark-resight framework increases precision compared to other analyses [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If density‐dependent factors and the rebound of cougars in the West has now brought populations to the edge of their current range in North America, perhaps our findings (specifically that of greater female dispersal rates and distances) are simply previously unseen observations. Recent research from South America (Zanón‐Martínez et al ) suggests that cougars use areas with less suitable characteristics during movements and Elbroch and Wittmer () reported cougars used open spaces with aggregate prey in the absence of other terrestrial predators. Given much of the grassland and agricultural landscape throughout the Midwest is largely devoid of other large, competing predators (i.e., gray wolves [ Canis lupus ], black bears [ Ursus americanus ]), perhaps this is an indication of what we might expect in the future, although much unoccupied habitat exists in the region for gray wolves and bears (Smith et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a temporary saline lake in a protected area (Parque Luro Provincial Reserve), where the current anthropogenic influence is relatively low, provides the opportunity to make comparisons with the most impacted lakes previously studied and to assess the magnitude of human influence. Several aspects of the ecology of the terrestrial flora and fauna of the reserve have been studied (Cano 1980;Maceda et al 2001;Sosa et al 2010;González-Roglich et al 2012;Zanón-Martínez et al 2016), and most of this information has been applied in its management (Subsecretaría de Ecología 2004). However, it is not the case for its aquatic ecosystems, on which only some hydrological information exists.…”
Section: Introductionmentioning
confidence: 99%